An introduction to the special issue: family violence and youth violence: examining the connections from interdisciplinary perspectives (an extension of Anna Costanza Baldry's legacy) - Hong, Jun Sung (Journal of family violence, 2021)
Family violence and youth violence have received a significant amount of research attention over the years. A large body of research findings has substantiated a significant association between experiences in family violence, such as maltreatment and exposure to parental violence, and youth violence, such as bullying, fighting, dating violence, gang violence. In honor of the late Dr. Anna Costanza Baldry, this special issue brings together scholars from a variety of disciplines (psychology, criminal justice, social work, and health science) to explore how family violence and youth violence are interrelated.